Fracture analysis of a low pressure steam turbine blade. (April 2016) - Plesiutschnig, Ernst; Fritzl, Patrick; Enzinger, Norbert; Sommitsch, Christof
Abstract : Highlights: The life time of steam turbine blades was limited by unsteady steam bending forces. The number of damaging loading conditions is estimated from the fatigue crack. Fracture mechanics, finite element analysis, literature and metallography are used. The cyclic bending stress and the time from and to a crack size is estimated. The number of fluid flux variations should be considered for inspection intervals. Abstract: Cracks were analysed at the root of the third blade row of low-pressure steam turbine blades of different natural frequencies. The root cause of the fatigue crack initiation was pitting corrosion of the forged ferritic/martensitic X20Cr13 material. Metallographic investigations, finite element analysis and fracture mechanics analysis combined with experimental data from the literature are used to evaluate crack propagating stresses to discuss the operating conditions. The calculations show that corrosion pits at the root of the turbine blade increase the local stresses above yield strength. Excitation of natural frequencies by changing the rotor speed is not responsible for the crack propagation. The centrifugal load and superimposed bending load caused by unsteady steam forces are responsible for the crack propagation.